2011
DOI: 10.1063/1.3604490
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Nano and Micro Fiber Structures in Ultrafine Particles Filtration

Abstract: Abstract. Selected procedures permitting to prepare homogeneous nanofibre structures of the desired morphology by employing a suitable combination of variables during the electrospinning process are presented. A comparison (at the same pressure drop) was made of filtration capabilities of planar polyurethane nanostructures formed exclusively by nanofibres, space polycarbonate nanostructures having bead spacers, structures formed by a combination of polymethyl methacrylate micro-and nanofibres and polypropylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…PU solution in (DMF), based on MDI, PAIM polymer diol, M w =2×10 3 g mol −1 ) and BD was synthesized at the molar ratio 9:1:8 (PU 918) at 90 °C for 5 h per partes way of the synthesis, starting with the preparation of a pre-polymer from MDI and PAIM, followed by adding BD and the remaining quantity of MDI. After being supplemented with BC to idealize conductivity, the solution was electrospun at a concentration of 13 wt% PU with M w =9.8×10 4 g mol −1 [50].…”
Section: Preparation Of the Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…PU solution in (DMF), based on MDI, PAIM polymer diol, M w =2×10 3 g mol −1 ) and BD was synthesized at the molar ratio 9:1:8 (PU 918) at 90 °C for 5 h per partes way of the synthesis, starting with the preparation of a pre-polymer from MDI and PAIM, followed by adding BD and the remaining quantity of MDI. After being supplemented with BC to idealize conductivity, the solution was electrospun at a concentration of 13 wt% PU with M w =9.8×10 4 g mol −1 [50].…”
Section: Preparation Of the Nanofibersmentioning
confidence: 99%
“…However, these studies have been solely limited to the filtration of single natural or synthetic hormones [1,15,48,49]. This highlights the necessity of developing the least fiber diameter optimized nanofibers to extract such estrogenic hormones simultaneously and then gauge their kinetics for comparison [50].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibres of different polymers, such as PU, PC, PA, and PVDF, were electrospun onto a spunbonded PP substrate or onto a commercial nonwoven fabric [96,97]. Electrospinning processes that allow spatial nanostructures with microspheres, as well as structures with a broad fibre distribution, have been reviewed by Kimmer et al [97].…”
Section: Special Filtering Structuresmentioning
confidence: 99%
“…Additionally, in our previous study, we have reported polyurethane (PU), cellulose acetate (CA), and polyacrylonitrile (PAN) for such estrogenic hormones (unpublished data). Hence, it is necessary to develop and optimize such nanofibers produced from recycling that can reduce litter, behave ideally for removing EH, and require low production cost (Kimmer et al 2011).…”
Section: Introductionmentioning
confidence: 99%